The effectiveness of sickle cell anemia treatment using CRISPR - Fahira, Adinda Putri Awalia; Widowati, Retno; Fajri, Hidayatul (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
The rapid advancement of medical biotechnology plays a crucial role in healthcare practices, particularly in genetic engineering for sickle cell anemia. Currently, there is no definitive cure for sickle cell anemia, but in recent years, gene therapy has been extensively researched as an alternative solution. Gene therapy trials on sickle cell anemia patients have been conducted using CRISPR technology, and its effectiveness is still under investigation. The principle involves manipulating the abnormal hemoglobin gene in erythrocytes, which causes sickle cell disease, by extracting stem cells from the patient’s bone marrow and replacing the faulty gene with a normal one using CRISPR (Clustered Regulatory Interspaced Short Palindromic Repeats). The critical components required are Cas9, an endonuclease restriction enzyme, and gRNA, which guides Cas9 to the target gene for manipulation. Once the target gene is successfully cut by Cas9, DNA polymerase naturally initiates a gene repair mechanism through the HDR (Homologue-directed repair) pathway, a process of repairing damaged DNA sequences in CRISPR. Based on tests conducted on 44 patients, 28 patients showed promising results, with their bone marrow producing functional, normal erythrocytes.